The relationship between the alcohol use patterns and cognitive and symptomatic functioning of Rhodes University students - Mayson, Tamara Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
Introduction: Studies reveal differential cognitive effects of alcohol use, with moderate to heavy alcohol having some beneficial effects in older adults, whereas in young adulthood, heavier alcohol use produces deficits. The aim of the research was to investigate the relationship between patterns of alcohol use and the cognitive and symptomatic functioning of university students over one year, and to discern which demographic, clinical and alcohol factors might moderate cognitive outcomes. Method: The sample included undergraduate Psychology students from a South African University, aged 18 to 23 years (n = 86). The sample was divided into two alcohol use groups based on four categories from the Alcohol Use Disorders Identification Test (AUDIT) (Babor et al., 2001), including a lighter drinking group (Safe/Hazardous, n = 74) and a heavier drinking group (Harmful/Dependent, n = 12). The two drinking groups were statistically equivalent for distribution of age, gender, English first language, race groups, history of neurological or psychiatric vulnerability, a measure of initial intelligence/cognitive reserve (Peabody Picture Vocabulary Test: PPVT-4) (Dunn & Dunn, 2007) and for a measure of test-taking validity (Immediate Postconcussion Assessment and Cognitive Test: ImPACT Impulse Control) (p = < 0.05 in all instances). Participants were tested on the computerized ImPACT battery (ImPACT, 2007) at three intervals over an academic year (May, August, October 2012). Repeated measures ANOVAs were used to investigate cognitive and symptomatic differences between the two alcohol use groups, in association with moderating factors. Results: The heavier drinking group revealed: (i) poorer performance on ImPACT Visual Motor Speed, Reaction Time and Cognitive Efficiency Index scores, including less ability to benefit from practice over time; (ii) symptom reports of severe Numbness/Tingling, Balance problems and Dizziness. Deleterious cognitive outcome was exacerbated by longer lifetime duration of alcohol use, passing out monthly, beer or wine drinking, smoking or substance use. Conclusion: Deleterious cognitive and symptomatic effects of heavy alcohol use are in evidence for undergraduate university students implicating current and/or cumulative alcohol induced brain impairment. The results of the study are of concern for optimal academic performance of students at an early stage of university level study, who engage in heavier (Harmful/Dependent) drinking patterns, with negative implications for future career attainment.
Keywords: Drinking of alcholic beverages -- South Africa; Rhodes University -- Students -- Alcohol use; Alcohol -- Physiological effect